Intraoperative lateral wall breach simulation in the cadaveric spine and the impact of thread designs of screws on pullout strength in the osteoporotic thoracic vertebrae: A biomechanical study in human cadavers - Ozcan Kaya; Okan Ozkunt; Mustafa Sungur; Mehmet Semih Cakir; Murat Baydogan; Kerim Sariyilmaz (Acta Orthopaedica et Traumatologica Turcica)
Objective: This study aimed (1) to simulate pedicle screw pullout after intraoperative external wall perforation and (2) to assess restoration strength with different thread designs in the pedicle screw instrumentation for osteoporotic thoracic vertebrae.